STRENGTHENING THE ROLE OF THE YOUNG GENERATION IN WELCOMING A GOLDEN INDONESIA THROUGH MANAGERIAL LEADERSHIP AND INNOVATION - Setyawibawa, Ruruh Aris (Bina Bangsa International Journal of Business and Management, 2024)
Golden Indonesia 2045 is the nation's grand vision in welcoming a century of independence with the hope of becoming a developed, highly competitive, and socially just country. The young generation as the main pillar of national development has a strategic role in realizing this vision. This article aims to examine how strengthening the role of the younger generation can be done through the development of visionary leadership and adaptive managerial innovation. The research method used is a literature study and qualitative analysis of various sources related to youth development, transformational leadership, and managerial strategies that are relevant in the context of globalization and the digital era. The results of the study show that empowering the younger generation through character education, leadership training, and the creation of an innovative ecosystem can accelerate the realization of Golden Indonesia. Synergy between governments, educational institutions, the private sector, and society is needed to create spaces for active participation and sustainable leadership for the younger generation. Thus, the young generation is not only the object of development, but the main subject who is able to lead change and innovation towards a glorious future of the nation